2011
DOI: 10.1200/jco.2010.31.1142
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib Plus CHOP-Rituximab for Previously Untreated Diffuse Large B-Cell Lymphoma and Mantle Cell Lymphoma

Abstract: PurposeThe proteasome inhibitor bortezomib may enhance activity of chemoimmunotherapy in lymphoma. We evaluated dose-escalated bortezomib plus standard cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) plus rituximab (R) in patients with diffuse large B-cell lymphoma (DLBCL) and mantle cell lymphoma (MCL).Patients and MethodsSeventy-six subjects with untreated DLBCL (n = 40) and MCL (n = 36) received standard CHOP every 21 days (CHOP-21) with R plus bortezomib at 0.7 mg/m2(n = 4), 1.0 mg/m2(n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
171
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 285 publications
(182 citation statements)
references
References 46 publications
4
171
1
6
Order By: Relevance
“…46 Since the addition of rituximab to polychemotherapy, no other treatments have shown greater benefit in these patients, although some clinical and preclinical trials have shown the efficacy of new combinations of drugs, including proteasome inhibitors. 6,7,30,43 Bortezomib-mediated proteasome inhibition profoundly affects the ER homeostasis and induces an ER stress response that leads to cell death, potentially overcoming the intrinsic resistance to chemotherapy. 44 The use of bortezomib, both as a single agent or in combination with a wide range of agents, is currently under investigation to improve survival in aggressive lymphomas.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…46 Since the addition of rituximab to polychemotherapy, no other treatments have shown greater benefit in these patients, although some clinical and preclinical trials have shown the efficacy of new combinations of drugs, including proteasome inhibitors. 6,7,30,43 Bortezomib-mediated proteasome inhibition profoundly affects the ER homeostasis and induces an ER stress response that leads to cell death, potentially overcoming the intrinsic resistance to chemotherapy. 44 The use of bortezomib, both as a single agent or in combination with a wide range of agents, is currently under investigation to improve survival in aggressive lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…44 The use of bortezomib, both as a single agent or in combination with a wide range of agents, is currently under investigation to improve survival in aggressive lymphomas. 6,9,14,47 Although bortezomib monotherapy is mainly ineffective in DLBCL cell lines, 29 the combination with immunochemotherapy has been shown to benefit a selected group of patients with relapsed or refractory ABC DLBCL 7 and in previously untreated patients with advance disease. 6 We have demonstrated that almost all of the DLBCL cell lines studied were primary resistant to bortezomib monotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations